“I’m Not Satiety Without Rice”: Phenomenological Study of Barrier and Weight Loss Efforts in Home Settings - Rohayati Rohayati; Wiwin Wiarsih; Astuti Yuni Nursasi (Unnes Journal of Public Health, 2023)
Background: The prevalence of obesity around the world is quite high. Obesity management takes a long time and is highly disciplined. This can increase the noncompliance to obesity treatment. Family is a support system that can help obesity management. The study was to explored family experiences regarding the efforts and barriers to obesity management in a home setting. Methods: This study used a descriptive phenomenological research design. The seventh family who lived in Depok City were selected using purposive sampling. Inclusion criteria include 1) having family members who are overweight/obese, 2) obese family members who do not have comorbid diseases, 3) participants who do not have a chronic disease A semi-structured interview was used to collect data. The data analysis used Colaizzi’s method. Results: Four themes emerged, including 1) nutrition management efforts, 2) weight loss efforts, 3) unhealthy nutritional behavior patterns, 4) desire to achieve normal conditions. Conclusion: Family plays an important role in obesity management in the home setting. Nurses can optimize the family by providing support for positive efforts that have been made. Family counseling is needed to reduce perceived barriers.